Teachers’ Beliefs on Technology Integration in English Language Teaching - Maharani, Adinda Dwi Putri; Hidayat, Nur (Institut Agama Islam Negeri Parepare, 2025)
This study aimed to investigate teachers' beliefs towards technology integration in English language teaching in the classroom and identify the factors that support and hinder them in using technology in English language teaching. The participants were five English teachers in one of the senior high schools in Central Java, Indonesia. The data was collected through observation and semi-structured interviews. The researchers conducted a thematic analysis to analyze the data. The findings indicated that the interaction between teachers and students plays an essential role in increasing students' participation and enthusiasm during the learning process. Moreover, the teachers’ beliefs contributed to affect the teachers’ attitudes to technology integration. Easy access to learning materials, communication, and coordination, effective distribution of learning materials, assignments, and questions, evaluating and providing quickly, and making the material more interesting became factors that support the teachers to implement technology in the classroom. Moreover, some of the barriers for teachers to use technology include distraction of students' focus, time constraints, limited technological capabilities, limited school internet facilities, and teachers' beliefs.